Traffic Noise Annoyance in the Population of North Mexico: Case Study on the Daytime Period in the City of Matamoros - Zamorano-González, Benito; Pena-Cardenas, Fabiola; Velázquez-Narváez, Yolanda; Parra-Sierra, Víctor; Vargas-Martínez, José Ignacio; Monreal-Aranda, Oscar; Ruíz-Ramos, Lucía (Frontiers in Psychology, 2021)
The presence of noise in urban environments is rarely considered a factor that causes damage to the environment. The primary generating source is transportation means, with vehicles being the ones that affect cities the most. Traffic noise has a particular influence on the quality of life of those exposed to it and can cause health alterations ranging from annoyance to cardiovascular diseases. This study aims to describe the relationship between traffic noise level and the perceived annoyance in a city's inhabitants on the Northern Border of Mexico. The work carried out in a city presents vulnerability characteristics: economic, social, and migratory of its inhabitants' sizable portion. Material and methods: The measurement of traffic noise considered streets and avenues with an annual average daily traffic of more than 1,000 vehicles per day. The equipment used was sound level meters and tripods. A questionnaire was applied to people living within 250 meters of the streets on which the noise was measured. Results: The noise measurement found a parameter of LAeq estimated for 12 hours during the day, exceeding 70 dBA. Statistic tested the data received from the questionnaire through Pearson correlation tests. A total number of 2350 people participated, of whom 1378 were female (58.6%) while 972 were men (41.4%). The age range was 18 to 75 years. The overall perception of traffic noise annoyance identified that 1131 participants (48.1%) responded that "Yes" they consider the noise annoying. Participants who said "No" as well as those who responded "Do not know" resulted in a total of 1219 people (51.9%). Conclusions: The results show that the population is desensitized to traffic noise and does not perceive it as an annoyance. The flow of vehicles and the type of vehicles are significant factors for the propagation and increase of traffic noise levels. Women present a considerable appreciation of traffic noise perception instead of younger people who demonstrate a higher tolerance to high-level exposure. As reflect the lack of information of the population around the noise problem and its effects.